Pelatihan Self-Efficacy Diet Kalori untuk Meningkatkan Perceived Behavioral Control sebagai Determinan Intensi Diet Kalori pada Pasien Diabetes Melitus Tipe II - Kristania Ruth Pratiknyo; Ida Ayu Nyoman Kartikawati; Henndy Ginting (Humanitas (Jurnal Psikologi), 2019)
Abstract This research intends to see the calorie intentions increasing with type II diabetes patients in Clinic "X" Bandung, after being given self-efficacy training of calorie diet. Theory and questionnaire based on the theory of planned behavior (Ajzen, 2005) and general self-efficacy (Schwarzer 1995). Analyzed data using a mixed-method in which combining quantitative and qualitative data (Creswell, 2016). Test the validity PBC of calorie diet and self-efficacy of calorie diets is done using content validity. The results are that after participating in self-efficacy training of calorie diet patients with type II DM at Clinic "X" Bandung showed an increase of the calorie diet PBC. Theoretical suggestion for subsequent research is to increase the number of research subjects so that the data obtained can be calculated statistically and it can show the significance of increased PBC of calorie diets in patients with type II DM at Clinic "X" Bandung. Doctors and nurses at Clinic"X" Bandung can use this training to help other DM patients so they can have self-efficacy in the calorie diet so that it can increase PBC to carry out diet calorie. Keywords: perceived behavior control (PBC), self-efficacy, calorie diet, DM type II